Role of magnesium in depression? - Petrović Jelena; Pešić Vesna; Popović Dejana; Plećaš Bosiljka (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2014)
Magnesium has a fundamental role in human body and it is necessary for many processes such as: transmembrane ion flux, neuronal activity, neurotransmitter release, regulation of adenylate cyclase and hormone receptor binding. In the central nervous system magnesium blocks the activity of NMDA receptors and magnesium-deficiency leads to NMDA receptors overactivity, possibly causing neuronal injury and neurological dysfunction, which consequently may manifest as major depression. Numerous pre-clinical and clinical studies confirmed that magnesium influences several systems associated with development of depression. On the other hand, standard antidepressants are ineffective in 40% of cases, and have some unpleasant side-effects. Even though the first positive effect of magnesium in patients with agitated depression was reported in 1921, unfortunately, only small number of studies that favor magnesium's effectiveness in treating depression was published in past decades, including one randomized clinical trial in which magnesium was as effective as imipramine in depressed elderly patients that suffered from diabetes. Even though much more clinical research is needed to extend this important line of research and to confirm its efficacy, due to its safety magnesium preparations could be considered as a potential addition for treatment resistant depression cases.